Legal Protection for Business Actors Regarding Shophouse (Ruko) Order Agreements at Sentraland Residence 2 Linked to Law Number 8 of 1999 Concerning Consumer Protection - Chicka Aircheny; Rahmatiar, Yuniar; Abas, Muhamad (Dinasti Research, 2024)
Along with the increase in the number of developments nowadays, there are many property sales, in the form of offices and even shophouses which can be used as investments and business ventures for buyers. Shop houses are often used as residences as well as places of business, with a sale and purchase agreement between the consumer and the business actor to provide optimal benefits for the parties if they comply with the obligations in accordance with the agreed agreement. However, consumers do not fulfill their obligations to make shophouse payments. Actions carried out by consumers constitute acts of breach of contract. The identification of this research problem is how legal protection is for business actors regarding the agreement to order the Sentraland Residence 2 shop house and what are the legal consequences for consumers who have bad intentions towards business actors. This research uses normative juridical research methods with a statutory approach and a case approach. The conclusion of this research is that legal protection for business actors can claim their rights if they are harmed by consumers by filing legal action for compensation and legal consequences for consumers who have bad intentions, so consumers make compensation payments to business actors through court decisions in the form of remaining payment obligations, insufficient installments, late fees, and other transaction fees.